Influência das plantas de cobertura nas características produtivas da alface e nos atributos físicos e químicos do solo - Pauletti, Daiana Raquel (2012)
A soil mulching change soil physical and chemical compounds and promotes benefits to lettuce production system. This study aimed to evaluate the effect of mulching on the yield characteristics of lettuce and continuous cultivation of these effects in the physical and chemical soil properties. The aim of this work was conducted from June 2010 to February 2011, in Santa Helena - Paraná. The experiment was conducted in two stages; the first step consisted of growing covering plants until they reach a cutoff point, initiating the second step consisting in the conduct of two consecutive cycles of the lettuce crop, produced on straw. The experiment was conducted in a randomized complete block design in split-split plots with four replications, the plots consist covering plants: oat (Avena strigosa Schreb), pearl millet (Pennisetum glaucum L.), turnip (Raphanus sativus L. var. Oleiferus Metzg), snap bean (Phaseolus vulgaris L.) and control (bare soil), the sub plots of lettuce cultivars (Vanda and Veronica) and subsubplot the lettuce crop cycles (first and second cycle). The lettuce was evaluated for plant height, head diameter, leaf number, fresh and dry mass of stems and leaves, leaf area, total dry weight (leaves + stem), stem diameter and crown projection. For cover covering were determined fresh and dry shoot. During the experiment were also evaluated, the physical attributes (density, macroporosity, micro porosity, total porosity, and resistance to moisture penetration) and chemical (pH, P, K, Ca +2, Mg +2, H +Al , sum of bases, base saturation and organic matter), the experimental area, at two depths and three sampling times. The presence of mulch benefited growing lettuce in the first cycle. The cultivar was superior to cultivate Veronica Vanda conditions of the study. The development of the lettuce crop was damaged due to high temperatures during the period of cultivation of the crop. The millet stood out as cover crop for the excellent potential for biomass. The percentage of macropores appeared above the minimum requirement (10%) required for proper root development of crops. The microporosity increased with the sampling depth, while the macroporosity decreased. The percentage soil moisture was proportional to the amount of weight produced by covering plants. As for soil chemical properties observed accumulation of P in the soil surface layer, the potential acidity (H + Al) tended to increase during the evaluation periods while pH showed some decrease with age, it was not found a significant difference to the levels of organic matter but they were higher in the surface layer